Globalization, creative destruction, and labor share change: Evidence on the determinants and mechanism from longitudinal plant-level data - Mika Maliranta; Petri Böckerman (The Research Institute of the Finnish Economy (ETLA), 2009)
We examine the sources and micro-level mechanisms of the changes in the labor share of value added. We link the micro-level dynamics of the labor share change with that of productivity and wage growth. Using a useful variant of the decomposition method we make a distinction between the change in the average plant and the micro-level restructuring. With Finnish plant-level data covering three decades we show that micro-level restructuring is the link between the declining labor share and increasing productivity in 12 manufacturing industries of four regions, and that increased international trade is a factor underlying those shifts.
Keywords: F16; J31; 330; Globalization; international trade; foreign ownership; micro-level restructuring; labor share; Lohnquote; Globalisierung; Außenwirtschaft; Multinationales Unternehmen; Wirtschaftliche Anpassung; Finnland